Limitations of Sustainability Certification on Good Agricultural Practices Adoption Among Certified and Noncertified Oil Palm Smallholders - Agung Rahmat Syahputra; Ratnawati Nurkhoiry; Rizki Amalia; Iput Pradiko (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2026)
Sustainability certifications are often regarded as tools for improving agricultural practices and supporting environmental stewardship among independent oil palm smallholders in Indonesia. However, their effectiveness in driving comprehensive agronomic transformation and improving household income remains debatable. This study examines the effect of sustainability certification on the adoption of Good Agricultural Practices (GAP) among certified and non-certified smallholders in the Philippines. We analyzed data from 64 oil palm smallholders in Simalungun Regency, Indonesia, using comparative and correlation statistical methods. The findings indicate that certification had a limited impact on core agronomic practices, such as fertilization, pruning, and weeding, which remain constrained by structural barriers, including limited technical capacity and financial resources. Certified smallholders exhibited better environmentally focused practices, particularly in reducing the use of hazardous chemicals and adopting sustainable weeding methods, although the differences were not statistically significant. These results suggest that certification programs have been more responsive to external market demands for environmental compliance but have fallen short in facilitating the widespread adoption of productivity-enhancing agronomic practices among smallholders in the region. To achieve environmental sustainability and improved productivity, future certification schemes should be designed to provide stronger agronomic support and balanced incentives. This study provides new insights into the limitations of sustainability certifications in driving comprehensive agronomic improvements, while highlighting their potential to address specific environmental challenges.